2017
DOI: 10.1002/pbc.26670
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of minichromosome maintenance protein 10 in medulloblastoma and its clinical implications

Abstract: Taken together, our study reveals that the pre-RC is dysregulated in MB. In addition, MCM10, a member of this complex, is significantly overexpressed in MB and is required for tumor cell proliferation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…MCM10 is a replication initiation factor that plays functions together with the MCM2‐7 helicase and the DNA polymerase alpha/primase complex . Previous studies have observed MCM10 is overexpressed in different types of human cancers, such as medulloblastoma, cervical cancer, and esophageal cancer . Furthermore, Li et al demonstrated that MCM2 and MCM10 were the two most significantly upregulated genes in urothelial carcinoma progression among the MCM gene family .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MCM10 is a replication initiation factor that plays functions together with the MCM2‐7 helicase and the DNA polymerase alpha/primase complex . Previous studies have observed MCM10 is overexpressed in different types of human cancers, such as medulloblastoma, cervical cancer, and esophageal cancer . Furthermore, Li et al demonstrated that MCM2 and MCM10 were the two most significantly upregulated genes in urothelial carcinoma progression among the MCM gene family .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies show MCM10 is often dysregulated under pathological conditions . Genetic amplification and/or overexpression of MCM10 were also observed in different types of human cancers . For instance, Cheng et al found a series of replicative helicase proteins, such as MCM10, MCM2, MCM4, MCM5, and MCM6 were overexpressed in cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…MCM10 was increased in medulloblastoma, urothelial carcinomas, prostate cancer and breast cancer [41][42][43][44] and finally, AUNIP was overexpressed in various brain tumors [45]. Conversely, respective expression of the 6 selected genes was downregulated by the three treatments in this study.…”
Section: Gene Expression Changes Related To Cancer Progressionmentioning
confidence: 61%
“…MCM10, along with CDC45-MCM2-7 complex, is a subtype of the MCM family relating to initiating DNA replication and regulating cell proliferation in late G1 or early S phase of cell cycle [16][17][18] . Accumulating studies have shown that MCM10 expression tended to be higher in a variety of malignancies [19][20][21][22][23] . Over-expression of MCM10 in some cancers had a close relationship with tumor progression and dismal clinical outcomes [19][20][21] .…”
Section: Introductionmentioning
confidence: 99%